Nhận thức và thực tiễn dạy học khám phá của giáo viên Khoa học: Một nghiên cứu khảo sát tại Việt Nam - Sái Công Hồng, Sái Công Hồng; Nguyễn Thị Thanh Tâm, Nguyễn Thị Thanh Tâm; Nguyễn Hoàng Gia Khánh, Nguyễn Hoàng Gia Khánh; Đào Thị Hoàng Hoa, Đào Thị Hoàng Hoa; Lê Hải Mỹ, Ngân (Tạp chí Giáo dục, 2026)
The 2018 Vietnamese General Education Curriculum emphasizes the development of scientific inquiry competency through active teaching approaches, among which inquiry-based learning (IBL) is considered an appropriate approach. However, science teachers in Vietnam still demonstrate considerable differences in their perceptions and implementation of IBL. This study employed a descriptive survey design combining quantitative and qualitative analyses to investigate teachers’ perceptions and practices regarding IBL. Teachers generally held positive perceptions of scientific inquiry competency and IBL, although differences remained regarding the role of hands-on experiments in developing this competency. While teachers reported frequently implementing activities related to scientific inquiry competency, most did not demonstrate a clear understanding of the IBL process in their descriptions of classroom practices. The major difficulties reported by teachers included limited facilities, large class sizes, differences in students’ abilities, and students’ learning attitudes. The implementation of IBL depends not only on teaching conditions but also on teachers’ understanding of the nature and process of IBL. The study highlights the need for professional development programs that support teachers in organizing IBL activities to foster scientific inquiry competency in the current school education context.